Handbook of water and wastewater treatment technologies - Cheremisinoff, Nicholas P. (Boston : Butterworth-Heinemann, 2002)
This Handbook is an authoritative reference for process and plant engineers, water treatment plant operators and environmental consultants. Practical information is provided for application to the treatment of drinking water and to industrial and municipal wastewater. The author presents material for those concerned with meeting government regulations, reducing or avoiding fines for violations, and making cost-effective decisions while producing a high quality of water via physical, chemical, and thermal techniques. Included in the texts are sidebar discussions, questions for thinking and discussing, recommended resources for the reader, and a comprehensive glossary. Two companion books by Cheremisinoff are available: Handbook of Air Pollution Control Technologies, and Handbook of Solid Waste Management and Waste Minimization Technologies. * Covers the treatment of drinking water as well as industrial and municipal wastewater * Cost-efficiency considerations are incorporated in the discussion of methodologies * Provides practical and broad-based information in one comprehensive source.
An Overview of Water and Wastewater; What Filtration Is All About; Chemical Additives that Enhance Filtration; Selecting the Right Filter Media; What Pressure- and Cake-Filtration Are All; Cartridge and Other Filters Worth Mentioning; What Sand Filtration is All About; Sedimentation, Clarification, Flotation, and Membrane Separation Technologies; Ion Exchange and Carbon Adsorption; Water Sterilization Technologies; Treating the Sludge; Glossary; Index.
Includes bibliographical references and index.
Keywords: Water -- Purification; Sewage -- Purification; Water -- Purification -- Filtration; Electronic books